2018
DOI: 10.1007/s10571-018-0614-5
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the Stress System with a Mifepristone Challenge

Abstract: Psychotic depression is characterized by elevated circulating cortisol, and high daily doses of the glucocorticoid/progesterone antagonist mifepristone for 1 week are required for significant improvement. Using a rodent model, we find that such high doses of mifepristone are needed because the antagonist is rapidly degraded and poorly penetrates the blood-brain barrier, but seems to facilitate the entry of cortisol. We also report that in male C57BL/6J mice, after a 7-day treatment with a high dose of mifepris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 130 publications
(209 reference statements)
0
24
0
Order By: Relevance
“…At a CORT125281 dose that was sufficient for effective antagonism, HPA-axis activity was relatively unaffected during basal and stressed conditions. Acute GR antagonism with mifepristone is known to further increase stimulated GC levels due to disinhibition of the HPA-axis (Gaillard et al 1984, De Kloet et al 1988, while chronic administration can lead to suppression of the HPAaxis (van den Heuvel et al 2016, Kroon et al 2018, Dalm et al 2019. In our study, we evaluated CORT125281 only in a continuous and not in an acute treatment regimen, which may have allowed for adaptation of HPA-axis responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…At a CORT125281 dose that was sufficient for effective antagonism, HPA-axis activity was relatively unaffected during basal and stressed conditions. Acute GR antagonism with mifepristone is known to further increase stimulated GC levels due to disinhibition of the HPA-axis (Gaillard et al 1984, De Kloet et al 1988, while chronic administration can lead to suppression of the HPAaxis (van den Heuvel et al 2016, Kroon et al 2018, Dalm et al 2019. In our study, we evaluated CORT125281 only in a continuous and not in an acute treatment regimen, which may have allowed for adaptation of HPA-axis responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The new data on prevention and/or reversal of stress-induced programming effects add to a growing body of evidence demonstrating that blockade of the GR can reset stress response patterns imposed by (early life) trauma and chronic stress. 144,145 Presently, there are two hypotheses to explain later life consequences of early experience. First, dysregulation and increased vulnerability can occur when later life experience does not match the early-life conditions: the match-mismatch hypothesis.…”
Section: Priming Of Coping Circuitsmentioning
confidence: 99%
“…176 Why some of these treatment schedules were effective, even beyond the context of the fearful experience might be explained by the remarkable capacity of glucocorticoid receptor modulation to reset the stress system. 145…”
Section: Gr and Downstream Genes Are Promising Biomarkers For Vulneramentioning
confidence: 99%
“…In the present study, we sought to use siRNAs to knockdown GR expression in the neonatal brain to investigate the role of endogenous brain GR in HI-induced inflammation in mild brain injury and short- and long-term neurobehavioral outcomes. Our rationale was based on the complex regulation of glucocorticoid and progesterone receptor observed with other GR antagonist, including mifepristone [24,25]. We have shown that intracerebroventricular (ICV) injection of GR siRNAs significantly downregulated GR expression in the neonatal rat brain, providing a model to explore the role of endogenous brain GR in the pathogenesis of HI injury in the neonatal brain.…”
Section: Discussionmentioning
confidence: 99%